A região do Médio Tietê e os primeiros acordes paulistas: o Cururu - Pazetti, Henrique Albiero [UNESP] (2014)
The Cururu is an ancient cultural tradition of the São Paulo region of the Middle Tietê and consists of a challenge between singers improvised verses of the sound of the viola caipira. As we understand music as a geographical attribute, we affirm that the landscape, the place, the region and the geographicity the Middle Tietê are on Cururu, just where the Cururu is a fundamental part of the constitution of this region. In carrying out this task on hold you for Humanistic Geography which allowed us to grasp the Cururu the existential route, intimate and organic way, seeking the essence of this culture by living places and talks with people who so strongly appreciate this rustic tradition